LEGAL LIABILITY OF NOTARIES INVOLVED IN DOCUMENT FORGERY: AN ANALYSIS OF COURT DECISION NO. 1362/PID.B/2019/PN JKT.UTR - Ayunda Putri Shalsabilla (YURIS: Journal of Court and Justice, 2025)
As public officials, notary have the authority to draw up authentic deeds that possess strong evidentiary value in the eyes of the law. However, abuse of this authority such as the falsification of documents by a notary poses serious problems within the legal system and undermines public trust in the notarial profession. This study aims to analyze the forms of legal accountability imposed on notaries proven to have falsified documents, from the perspectives of criminal law, civil law, and professional ethics. The research method employed is normative juridical, using statutory and case study approaches. The results indicate that notaries who are legally and convincingly proven to have committed document falsification may be subject to criminal sanctions under the Indonesian Criminal Code (KUHP), civil liability for damages caused to affected parties, as well as administrative and ethical sanctions from the Notary Supervisory Council. Firm law enforcement and effective oversight mechanisms are essential to prevent similar violations and to uphold the integrity of the notarial profession.